(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article is about the use of modern electronic systems in the provision of transport services to the population of the city and the convenience of the population. Improving the efficiency of urban passenger transport management is a topical issue today. Therefore, the organization of proper traffic and improving traffic safety is a solution to the current problem.